The Impact of Entrepreneurship Education, Creativity, and Intrinsic Motivation on Entrepreneurial Intention: A Mediation Study of Student Self-Efficacy in Indonesia - Judijanto, Loso; Sukmayadi, Dodi; Sono, Mohammad Gifari; Hibrida, Anas Romzy; Mardiah, Ainil (Westscience Press, 2025)
This study investigates the effects of Entrepreneurship Education, Creativity, and Intrinsic Motivation on Entrepreneurial Intention among students in Indonesia, with a focus on Self-Efficacy as a mediating variable. A quantitative research approach was employed, using a sample of 170 students. The data were analyzed through Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The results revealed that Creativity (β = 0.553), Entrepreneurship Education (β = 0.336), and Intrinsic Motivation (β = 0.769) all significantly influence Entrepreneurial Intention. Additionally, Self-Efficacy was found to mediate the relationships between these variables and Entrepreneurial Intention. These findings highlight the importance of fostering creativity, enhancing entrepreneurship education, and supporting intrinsic motivation to increase students' entrepreneurial intentions. The study emphasizes the critical role of self-efficacy in shaping students' entrepreneurial behavior and provides insights for educational institutions and policymakers to develop effective strategies for promoting entrepreneurship among students.